Portfolio diversification across cryptocurrencies and ASEAN-5 currencies - Chen, Li Ern (2024)
This paper investigates the dynamic between the movement of top five cryptocurrencies including Bitcoin (BTC), Ethereum (ETH), Litecoin (LTC), Ripple (XRP), Cardano (ADA) and the ASEAN-5 currencies (MYR, THB, PHP, SGD, THB) against USD from 1st January 2020 to 31st May 2023, since the popularity of cryptocurrencies has increased within ASEAN countries. The results show that Ripple is positively correlated and statistically significant with IDR while the relationship between cryptocurrencies and ASEAN-5 currencies are not statistically significant and the findings show a very weak correlation and even negative correlation between each other. In order to have further clarification whether cryptocurrencies can be used to diversify ASEAN-5 currencies portfolio, Modern Portfolio Theory (MPT) by Markowitz is being applied by generating global minimum variance portfolio (GMVP). The portfolios are optimised using minimum variance. The results demonstrate that the GMVP with both cryptocurrencies and ASEAN-5 currencies have a better Sharpe ratio compared to the GMVP with only ASEAN-5 currencies but still the performance is not as good as expected. The investors can consider using cryptocurrencies to diversify their portfolios in order to lower their losses.